1997
DOI: 10.1177/019262339702500604
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Linked Toxic Responses to Dietary Iron Overload

Abstract: Genome-related differences to Fe overload between and within rodent species were evaluated in the present study. Male B6C3F1 mice, yellow and black C5YSF1 mice, and Fischer 344 (F344) rats were fed AIN-76A diets containing 35 (control), 1,500, 3,500, 5,000, or 10,000 micrograms carbonyl Fe/g for 12 wk. No effects on body weight gain were observed in the B6C3F1 and black C5YSF1 mice, whereas at all doses of Fe above the control, weight gain was reduced in yellow C5YSF1 mice and F344 rats. At the 10,000 microgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…The effect of iron overloading on bone resorption has not been subjected to biochemical or histomorphometrical study, although much effort has been expended in trying to clarify the mechanism of toxic or carcinogenic effects of iron on the liver, kidney, and other organs by detailed histopathology of iron toxicity (4,8,9,12,17,18,20,32,36,37,40). We observed bone loss of the secondary spongiosa in rats in a preliminary 3-month toxicity study of iron-lactate and conducted the present study to induce bone lesions and clarify the early changes using histomorphometry and biochemical markers of bone turnover.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of iron overloading on bone resorption has not been subjected to biochemical or histomorphometrical study, although much effort has been expended in trying to clarify the mechanism of toxic or carcinogenic effects of iron on the liver, kidney, and other organs by detailed histopathology of iron toxicity (4,8,9,12,17,18,20,32,36,37,40). We observed bone loss of the secondary spongiosa in rats in a preliminary 3-month toxicity study of iron-lactate and conducted the present study to induce bone lesions and clarify the early changes using histomorphometry and biochemical markers of bone turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Given that we and others have demonstrated that iron overload is associated with increased hepatocyte proliferation [20][21][22], which would be expected to cause telomere shortening, the finding that telomere lengths were not dramatically altered by iron loading suggested that telomerase activity might be increased in the iron loaded livers. Indeed, telomerase activity in the iron-loaded livers was increased 3-fold relative to control livers (p<0.05), in which there were detectable but rather low levels of telomerase activity, consistent with previous reports (Fig.…”
Section: Effect Of Iron Loading On Telomerase Activitymentioning
confidence: 71%
“…The data were obtained from five independent experiments. The level of significance was set at ***P<0.001, **P<0.01, and * P<0.05 impaired spermatogenesis, epididymal lesions, and impaired reproductive performance [8,25,26]. Iron overload often leads to testicular and seminal oxidative stress (OS) contributing to infertility [25].…”
Section: Discussionmentioning
confidence: 99%